2018
DOI: 10.1186/s11671-018-2654-7
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of High Specific Surface Carbon Nitride for Adsorption-Enhanced Photocatalytic Performance

Abstract: TMC-incorporated carbon nitride (CN) with hexagonal and quadrangle honeycomb-like structure and having periodic lattice defects linked by –CONH– bond was synthesized through combining the high calcination with the chemical condensation of melamine and 1,3,5-benzenetricarbonyl trichloride. The obtained CN has a tri-s-triazine ring and benzene ring skeleton, which makes it have excellent mechanical and thermal stability. The BET specific surface area was enhanced to about 125.6 m2/g, and the mean pore size is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The synthesized samples of carbon nitride were subjected to thermogravimetric study in nitrogen atmosphere in order to characterize their thermal stability. According to the DTG (derivative thermogravimetry) profiles (Figure 9), all samples obtained were thermally stable up to~600 • C. Above this temperature carbon nitride undergoes gradual decomposition mainly to N 2 , NH 3 , (CN) 2 , and HCN [60,61]. The samples obtained from dicyandiamide and melamine (Figure 9a) were considerably more stable than those obtained from thiourea.…”
Section: Thermogravimetric Analysismentioning
confidence: 98%
“…The synthesized samples of carbon nitride were subjected to thermogravimetric study in nitrogen atmosphere in order to characterize their thermal stability. According to the DTG (derivative thermogravimetry) profiles (Figure 9), all samples obtained were thermally stable up to~600 • C. Above this temperature carbon nitride undergoes gradual decomposition mainly to N 2 , NH 3 , (CN) 2 , and HCN [60,61]. The samples obtained from dicyandiamide and melamine (Figure 9a) were considerably more stable than those obtained from thiourea.…”
Section: Thermogravimetric Analysismentioning
confidence: 98%
“…1(c)), respectively, which confirmed the mesoporous framework of P-g-C 3 N 4 with porous monolayers forming a 3D architecture. 30,31…”
Section: Resultsmentioning
confidence: 99%
“…The basic skeleton structure of g-C3N4 consists of tri-s-triazine units connected with tertiary amino groups, which owns regularly distributed triangular water-selective permeation nanopores throughout the entire laminar structure.16 ,17 Moreover, the spacers between the g-C3N4 nanosheets, which interact with each other through weak van der Waals forces, also provide nanochannels for water transport while bigger molecules are retained. 18,19 Owing to this unique nanosheet structure, g-C3N4 exhibited many useful properties with applications in many fields, such as materials for membrane separation,20 ,21 photocatalysis,22 ,23,24 and electronic devices.25 g-C3N4 shows other advantages for CO2 photo-reduction because it is rich of N basic sites, which favour the CO2 adsorption step. Because of these outstanding properties, several reports were published on different synthetic strategies affording specific crystal phase, surface area, energy bands position and band gap energy.26 ,27 The synthesis of composite hybrid materials was explored to improve photocatalytic activity, taking advantage of the complementary features of inorganic and organic photocatalysts.28 Composites of g-C3N4 and TiO2 have shown superior photocatalytic activity by the formation of an artificial photocatalytic Z-scheme.29 ,30,31 They were used for various applications including CO2 reduction.32 ,33,34,35 Very recently, Petit et al, 28 reported on the use, for the first time, of TiO2/C3N4 nanosheet nanocomposites for CO2 photoreduction under UV-visible irradiation using H2 as sacrificial agent, demonstrating that the photocatalytic reduction of CO2 could be improved greatly by forming composite materials with increased CO2 adsorption capacity and which can suppress electron-hole recombination by facilitation of charge transfer.…”
Section: Accepted Manuscriptmentioning
confidence: 99%